2022
DOI: 10.3389/fmicb.2022.884880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat River Microbiome on the Symbiotic Microbiota and Multi-Organ Gene Expression of Captive-Bred Chinese Giant Salamander

Abstract: The reintroduction of captive-bred individuals is a primary approach to rebuild the wild populations of the Chinese giant salamander (Andrias davidianus), the largest extant amphibian species. However, the complexity of the wild habitat (e.g., diverse microorganisms and potential pathogens) potentially threatens the survival of reintroduced individuals. In this study, fresh (i.e., containing environmental microbiota) or sterilized river sediments (120°C sterilized treatment) were added to the artificial habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Proteobacteria and Firmicutes showed increased relative abundances in cultured Chinese giant salamanders infected with ADRV compared with those of healthy individuals, and the relative abundances of Bacteroidetes and Actinobacteria were lower in the diseased group. This seems to indicate that apart from Proteobacteria ( Woodhams et al, 2007 ; Zhu et al, 2022 ), Firmicutes is also related to amphibian defense and immunity. Additionally, Acidobacteria showed an increased relative abundance and ranked fifth in the diseased group, replacing Verrucomicrobiota, which ranked fifth in the healthy group and ranked down to sixth in diseased group.…”
Section: Discussionmentioning
confidence: 98%
“…Proteobacteria and Firmicutes showed increased relative abundances in cultured Chinese giant salamanders infected with ADRV compared with those of healthy individuals, and the relative abundances of Bacteroidetes and Actinobacteria were lower in the diseased group. This seems to indicate that apart from Proteobacteria ( Woodhams et al, 2007 ; Zhu et al, 2022 ), Firmicutes is also related to amphibian defense and immunity. Additionally, Acidobacteria showed an increased relative abundance and ranked fifth in the diseased group, replacing Verrucomicrobiota, which ranked fifth in the healthy group and ranked down to sixth in diseased group.…”
Section: Discussionmentioning
confidence: 98%
“…This can explain the observations that few infected CGSs were detected in the field ( Liu et al, 2021 ). Accordingly, pre-exposure to the field water conditions of CGSs before reintroduction can be an effective approach to help the colonization of diverse microbes, and thus enhance the survival of released individuals ( Zhu et al, 2022 ). This is especially true for the juveniles, as we found that released juveniles exhibited lower alpha diversity of microbiome than adults.…”
Section: Discussionmentioning
confidence: 99%
“…The brain transcriptome was included as the brain is a central organ in the regulation of pigmentation in amphibians. Previously-described protocols were followed for RNA extraction, purification, cDNA library construction, filtration, assembly, annotation, and gene expression quantification ( 23 ). RNA-seq was performed on an Illumina HiSeq 4000 platform by Annoroad (Beijing); paired-end reads were generated.…”
Section: Methodsmentioning
confidence: 99%